Bibliometric study on environmental, social, and governance research using CiteSpace - Zhao, Xiangying; Nan, Dongyan; Chen, Chaomei; Zhang, Shunan; Che, ShaoPeng; Kim, Jang Hyun (Frontiers in Environmental Science, 2023)
This paper offers an overview of the status of and emerging trends in environmental, social, and governance (ESG) research through a bibliometric approach using CiteSpace. In particular, our study aimed to elucidate the overall intellectual structure of the ESG academic field. To this end, we performed a topic search related to the ESG field and gathered published articles (2007–2021) from the Web of Science. Subsequently, we identified productive authors, institutes, and countries/regions to determine main research forces in the ESG field. Additionally, we conducted a co-citation analysis to identify highly cited authors, journals, and literatures in the ESG field. Furthermore, we performed a literature-co-citation-based cluster analysis and literature citation burst analysis to confirm the main themes and hotspots of the ESG field. These analyses can contribute to the investigations of key contributing forces in the ESG field at the author, institution, country/region, and journal levels and provide insights into the knowledge structures and orientations of the ESG field for future research.